A research framework of the halal certification role in purchase intention of Muslim consumers on the food products from Muslim majority countries in the Middle East and North Africa - Perdana, Firdaus Fanny Putera; Jan, Muhammad Tahir; Altunişik, Remzi; Jaswir, Irwandi; Kartika, Betania (International Journal of Modern Trends in Business Research, 2018)
The objective of this paper is to uncover the role of Halal certification in the purchase intention of Muslim consumers on food products from Muslim majority countries in the Middle East and North Africa. There is a certain belief that all the food products from the mentioned region are assumed Halal (Kullu Halal) as the majority of the population is Muslim. The fact that most these countries also import products from non-Muslim countries and the presence of the non-Halal food products in the country make the researcher believes that it is important to investigate the Halal status of the products and the consumer demand towards Halal certification when it comes to their purchase decision. A Halal certification is a form of safety for the Muslim consumers as the presence of it will ensure that the food products are safe for their consumption. The paper will propose a framework with Theory of Planned Behaviour as a basic theory. The issues encountered in the Halal certification demand are mostly related to Health, Animal Welfare, Religiosity and Food Safety (Halal Certification Motives). Those motives will be the factors that trigger the demand for Halal certification while Food Types and Foreign Ingredients will be the moderating factors between the Halal Certification Motives and Attitude. The researcher believes that it is imperative to study about Halal certification towards Food Products from Muslim Majority countries in the Middle East and North Africa as the studies about the Halal certification in the certain region are almost non-existent and there are actually some issues need discussion and to be solved. The study is limited to the conceptual framework of the consumer purchase decision towards the food products without Halal certification imported from the Muslim Majority countries in the Middle East and North Africa. Empirical research and non-empirical research must be performed to uncover the issues regarding the demand for Halal certification and the reasons why it is important to attach Halal certification in the Food Products. The comparison studies in the Muslim Majority countries, Multi-cultural countries, and Non-Muslim Majority countries must also be conducted to test the level of demand and awareness of the consumers living there. The results of the study are expected to provide some guidelines to the Muslim majority countries in the Middle East and North Africa region and help them strategize in increasing the sales of their food products.